How the farming of endangered species can save them from extinction - Hyland, Ross, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
My focus will be on three ranching operations in New Zealand (NZ). 1. Ngamatea (33,000 Hectares, 80,000 acres) is located south of Lake Taupo in the central North Island. Ngamatea is a large sheep and cattle farm and in addition have a tremendous commercial hunting and fishing operation. The 1500 wild Sikadeer on Ngamatea a very rare in NZ and Hunting Manager Bruce Bates says that since developing managed programmes, the average Sika carcase weights have nearly doubled. 2. Mesopotamia (26,000 Hectares, 64250 acres) is located at the headwaters of the Rangitata River in Canterbury NZ. 5000 Ha's is dedicated to commercial farming of Merino sheep, cattle and red deer for meat and velvet. Mesopotamia has a hunting concession over a further 21,000 hectares of the rugged Southern Alps of NZ where they breed and manage the very rare Himalayan Thar. These amazingly agile animals are incredibly elusive and spend most of their time high up in the jagged mountains of the 'Two Thumbs Range'. 3. High Peak (4000 Hectares, 10,000 acres) is located North of Lake Coleridge in NZ's Southern Alps. Commercially farm sheep, beef and deer with an additional 4,500 acre Red Deer trophy hunting block. High Peak has some of the greatest Red Deer anywhere in the world, but it is the owner's attention to detail and management of their deer populations that result in such magnificent trophies for their clients.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.